Alternative method for determining the consistency of coating mortars (Research, Society and Development, 2023)
Workability of coating mortars is directly linked to the quality of the application and adherence to the substrate, being the main property to be considered in the fresh state. Laboratory equipment is expensive and often does not fit into the budget of universities. It is proposed to evaluate an alternative method for determining consistency indexes in coating mortars, with a view to expanding access to research development. Two coating mortar mixes were produced, in proportions of 1:1:6 (A-T1) and 1:2:9 (A-T2) in cement, hydrated lime and sand, and compared with an industrialized mortar (A-IND). Developed and calibrated, the adapted equipment was used in the consistency tests and the water/binder ratios were defined. Cylindrical specimens were molded to evaluate the compressive strength. The mechanical test data were used in the analysis of variance and Tukey's test. Using 260 ± 5 mm spreads, the compressive strength did not show a significant difference between the industrialized mortar and the A-T1 mortar, a parameter that confirms the applicability of the method.